Structural and mechanistic studies on the peroxisomal oxygenase phytanoyl-CoA 2-hydroxylase (PhyH). - Schofield, C; McDonough, M (2007)
Phytanic acid (PA) is an epimeric metabolite of the isoprenoid side chain of chlorophyll. Owing to the presence of its epimeric beta-methyl group, PA cannot be metabolized by beta-oxidation. Instead, it is metabolized in peroxisomes via alpha-oxidation to give pristanic acid, which is then oxidized by beta-oxidation. PhyH (phytanoyl-CoA 2-hydroxylase, also known as PAHX), an Fe(II) and 2OG (2-oxoglutarate) oxygenase, catalyses hydroxylation of phytanoyl-CoA. Mutations of PhyH ablate its role in alpha-oxidation, resulting in PA accumulation and ARD (adult Refsum's disease). The structure and function of PhyH is discussed in terms of its clinical importance and unusual selectivity. Most point mutations of PhyH causing ARD cluster in two distinct groups around the Fe(II)- and 2OG-binding sites. Therapaeutic possibilities for the treatment of Refsum's disease involving PhyH are discussed.